A T-type Ca2+ current underlies low-threshold Ca2+ potentials in cells of the cat and rat lateral geniculate nucleus. - Crunelli, V (1989)
1. The characteristics of a transient inward Ca2+ current (IT) underlying low-threshold Ca2+ potentials were studied in projection cells of the cat and rat dorsal lateral geniculate nucleus (LGN) in vitro using the single-electrode voltage-clamp technique. 2. In cat LGN slices perfused at 25 degrees C with a solution which included 1 mM-Ca2+ and 3 mM-Mg2+, IT could be evoked by depolarizing voltage steps to -55 mV from a holding potential (Vh) of -95 mV and was abolished by reducing [Ca2+]o from 1 to 0.1 mM. IT was also blocked by 8 mM-Mg2+ and 500 microM-Ni2+, but 500 microM-Cd2+ was a significantly less effective antagonist. 3. The inactivation of IT, which occurred at Vh positive to -65 mV, was removed as Vh approached -100 mV. The process of inactivation removal was also time dependent, with 800-1000 ms needed for total removal. Activation curves for IT showed a threshold of -70 mV and illustrated that IT was extremely voltage sensitive over the voltage range from -65 to -55 mV. 4. The decay phase of IT followed a single-exponential time course with a time constant of decay which was voltage sensitive and ranged from 20 to 100 ms. The mean peak conductance increase associated with IT was 8.4 nS (+/-0.9, S.E.M.). 5. In more 'physiological' conditions (35 degrees C and 1.5 mM-Ca2+, 1 mM-Mg2+) the voltage dependence of activation and inactivation were unaffected. However, the development and decay of IT proceeded more rapidly and only 500-600 ms were needed for total removal of inactivation. Under these conditions, the use of voltage ramps showed that depolarization rates of greater than 30 mV/s were necessary for IT activation. 6. The use of multiple voltage-step protocols illustrated that the process of inactivation removal was rapidly reversed by brief returns to a Vh of -50 mV. Furthermore, any delay in IT activation, once the LGN cell membrane potential was in the IT activation range, resulted in a current of reduced amplitude. 7. Although IT in rat LGN cells was briefer and had a shorter latency to peak, it was otherwise similar to that seen in cat LGN cells. 8. The characteristics of IT are very similar to those of the T-type Ca2+ currents of other excitable membranes. The properties of IT are discussed with respect to its role in generating the low-threshold Ca2+ potentials which are central to the oscillatory behaviour of thalamic projection cells.